Analysis of cooling load on commercial building in UAE climate using building integrated photovoltaic façade system. (15th March 2020) - Salameh, Tareq; Assad, Mamdouh El Haj; Tawalbeh, Muhammad; Ghenai, Chaouki; Merabet, Adel; Öztop, Hakan F.
Highlights: Energy consumption and cost are studied for commercial office building in UAE. Two different cases were simulated namely, PV and BIPV. The PVsyst software was used to determine the best orientation for façade solar PV. Using BIPV, saved the annual air conditioning consumption by 17.3%. Abstract: In this study the details of energy consumption and its cost were studied and analyzed for a commercial office building in United Arab Emirates (UAE) as hot, dry and humid region where the cooling load is very high. Two different cases were simulated namely (a) base case without photovoltaic (PV) with normal glass windows (b) building integrated photovoltaic (BIPV) façade system with transparent PV windows. The building size, space layout, dimensions, shape and orientation for both cases were exactly the same. The PVSYST software was used to determine the best orientation for BIPV façade system installation to minimize the cooling load and maximize the electrical energy production. The amorphous silicon thin film was used for case (b) along with the weather data for the building location in Sharjah, UAE. The cooling load inside the building and its cost were evaluated for both cases. The use of BIPV façade system case in hot, dry and humid region saved the annual electrical consumption for the air conditioning system by 27.69% while it reduced the yearly energy cost by US 2084. Such a study would offer data at critical climate conditions necessary for the design and future implementation of this system in the Emirate of Sharjah.